Neurotoxic Dorsal CA1 Lesions versus 4 VO Ischaemic Lesions: Behavioural Comparisons - J. A. Nunn; J. A. Gray; H. Hodges (Behavioural Neurology, 1999)
Anterograde amnesia, a common consequence of transient cerebral ischaemia, has been attributed to cell loss in the hippocampal CA1 subfield. However, variable, widespread damage outside hippocampal CA1 can also occur following ischaemia. We compared the functional consequences of ischaemia and ibotenate acid CA1 lesions on 2 spatial memory tasks (water maze ‘place’ and ‘matching-to-position’) to address the possibility that extra-CA1 loss contributes to ischaemia-induced memory deficits in the rat. During place task acquisition, ischaemic rats showed deficits on more measures than ibotenic rats, and during a 1 min probe trial, only ischaemic rats were impaired. On the matching-to-position task, ibotenic rats showed greater impairment than ischaemic rats in terms of one-trial learning, whereas ischaemic rats were more impaired after Trial 2. Ischaemia and ibotenic acid lesions resulted in equivalent CA1 loss, but silver impregnation revealed additional extra-CA1 cell loss in ischaemic rats. Together with the greater behavioural deficits of ischaemic rats, these data indicate a role for extra-CA1 cell loss in ischaemia-induced memory impairments in both animals and humans.